2020
DOI: 10.3389/fmicb.2020.01463
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory Microbiome in Cystic Fibrosis: Compartment Patterns and Clinical Relationships in Early Stage Disease

Abstract: We compared the bacterial microbiomes lodged in the bronchial tree, oropharynx and nose of patients with early stage cystic fibrosis (CF) not using chronic antibiotics, determining their relationships with lung function and exacerbation frequency. CF patients were enrolled in a cohort study during stability and were checked regularly over the following 9 months. Upper respiratory samples (sputum [S], oropharyngeal swab [OP] and nasal washing [N]) were collected at the first visit and every 3 months. 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Also, the microbes have an ability to integrate exogenous DNA to withstand the selective pressure of antibiotics. Thus, in order to understand these dynamics, there have been various efforts to understand the correlation of genotype and phenotype (e.g., response to antibiotics) by several researchers ( Mena et al, 2008 ; Hazan et al, 2014 ; Macia et al, 2014 ; Sousa and Pereira, 2014 ; Kos et al, 2015 ; Jaillard et al, 2017 ; Lozano et al, 2018 ; Garcia-Nuñez et al,2020 ). Furthermore, the MLST profiles derived from two different tools-PubMLST and EPISEQ and the phenotypic antibiotic susceptibility profiles shows disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the microbes have an ability to integrate exogenous DNA to withstand the selective pressure of antibiotics. Thus, in order to understand these dynamics, there have been various efforts to understand the correlation of genotype and phenotype (e.g., response to antibiotics) by several researchers ( Mena et al, 2008 ; Hazan et al, 2014 ; Macia et al, 2014 ; Sousa and Pereira, 2014 ; Kos et al, 2015 ; Jaillard et al, 2017 ; Lozano et al, 2018 ; Garcia-Nuñez et al,2020 ). Furthermore, the MLST profiles derived from two different tools-PubMLST and EPISEQ and the phenotypic antibiotic susceptibility profiles shows disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increasing number of studies reveal an association between pulmonary microbiota (or dysbiosis) and lung diseases. These diseases include chronic obstructive pulmonary disease (COPD), asthma, cystic fibrosis, and idiopathic pulmonary fibrosis (IPF) 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…These diseases include chronic obstructive pulmonary disease (COPD), asthma, cystic fibrosis, and idiopathic pulmonary fibrosis (IPF). [4][5][6][7] Furthermore, some microbiomes have been linked to cancer. For example, infection with Helicobacter pylori (H. pylori), Fusobacterium nucleatum, human papilloma virus, and Escherichia coli can lead to various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, reduced bacterial diversity and increased dominance of certain species, particularly S. aureus and H. influenzae, correlates with antibiotic use, age and heightened inflammation [7,129,132,133]. From late childhood onwards Mycobacterium abscessus, Burkholderia cenocepacia and Pseudomonas aeruginosa begin to dominate and are strongly associated with disease progression [134][135][136][137][138][139]. Nevertheless, recent culture-independent studies have found that both the early stage and adult CF lung is more polymicrobial than previously thought [140,141].…”
Section: Cystic Fibrosismentioning
confidence: 99%